2008
DOI: 10.1007/s00108-007-1990-y
|View full text |Cite
|
Sign up to set email alerts
|

Antidementiva – wem nützen sie wirklich?

Abstract: Due to the heterogeneous course of illness in individual cases, efficacy or "treatment-response" can not be measured in single patients; therefore a clinical distinction between response and non-response is not meaningful. Constructs which are valid for research projects become misnomers in clinical practice. To date there are two groups of antidementia drugs, memantine--an NMDA-receptor modulator licensed for the moderate to severe stages--and the cholinesterase inhibitors donepezil, galantamine, and rivastig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…This was found to be the case for both GP and NP patients. Other studies have shown that antidementia drugs protect against cognitive and functional decline (Atri et al 2013;Förstl 2008;Koch et al 2005;Lopez et al 2002;Reisberg et al 2003;Rogers et al 1998;Sano et al 2003). One possible explanation for our finding is that the prescription of antidementia drugs was an indicator of the severity of the disease: i.e., that the patients in our study who were more affected by dementia were more likely to be prescribed antidementia drugs, but also had an increased risk of LTC.…”
Section: Discussionmentioning
confidence: 47%
See 4 more Smart Citations
“…This was found to be the case for both GP and NP patients. Other studies have shown that antidementia drugs protect against cognitive and functional decline (Atri et al 2013;Förstl 2008;Koch et al 2005;Lopez et al 2002;Reisberg et al 2003;Rogers et al 1998;Sano et al 2003). One possible explanation for our finding is that the prescription of antidementia drugs was an indicator of the severity of the disease: i.e., that the patients in our study who were more affected by dementia were more likely to be prescribed antidementia drugs, but also had an increased risk of LTC.…”
Section: Discussionmentioning
confidence: 47%
“…Moreover, our study did not distinguish between the use of cholinesterase inhibitor and memantine therapies. Whereas cholinesterase inhibitors are approved for mild to moderate Alzheimer's disease, memantine is used to treat the more severe forms (Förstl 2008). Thus, if it was possible to differentiate between these two medications, using them as indicators for the severity of the illness, we may be able to resolve this apparent contradiction.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations